Refining Coded Image in Human Vision Layer Using CNN-Based Post-Processing - Shindo, Takahiro; Tatsumi, Yui; Watanabe, Taiju; Watanabe, Hiroshi (IEEE Global Conference on Consumer Electronics, 2024)
Scalable image coding for both humans and machines is a technique that has gained a lot of attention recently. This technology enables the hierarchical decoding of images for human vision and image recognition models. It is a highly effective method when images need to serve both purposes. However, no research has yet incorporated the post-processing commonly used in popular image compression schemes into scalable image coding method for humans and machines. In this paper, we propose a method to enhance the quality of decoded images for humans by integrating post-processing into scalable coding scheme. Experimental results show that the post-processing improves compression performance. Furthermore, the effectiveness of the proposed method is validated through comparisons with traditional methods.